Effects of milk products (casein and lactose) on nutrient digestibility in weaned pigs fed a high fat dry diet - W H Turlington; G L Allee; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1987)
Two trials using a total of 48 pigs were conducted to compare protein (soybean meal and casein) and carbohydrate (dextrose and lactose) sources. In trial 1, digestion studies were conducted to determine apparent digestible energy content of the four treatments and apparent nutrient digestibility coefficients. In trial 2, pigs were sacrificed to determine ileal and total tract (apparent) nutrient digestibility coefficients. Results suggest that milk products are important to improving energy and nutrient digestibility in the young pig. The younger the pig or the sooner after weaning, the greater the benefit from their addition. The data also suggest that milk protein is of greater value in improving nutrient utilization than milk carbohydrate.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Casein; Lactose; Digestibility